Water hyacinth second-generation ethanol production: a mitigation alternative for an environmental problem - Giovana Roberta Francisco Bronzato; Sábrina Martina Ziegler; Rita de Cássia da Silva; Ivana Cesarino; Alcides Lopes Leão (Journal of Natural Fibers, 2019)
Natural fibers are very abundant, especially those derived from water plant as water hyacinth. The water hyacinth, which is rich in cellulosic fiber content, has a great ability to adapt itself to harsh conditions and at very high growth rate. Therefore, it is considered a pest due to environmental and economical damage to water bodies. A proposed alternative to mitigate the excessing water hyacinth problem is to use its biomass aiming the production of second-generation ethanol (2G), using cellulose as feedstock. It was been implemented different methods to optimize the production of 2G from water hyacinth. Two approaches were considered: a separate chemical pretreatment process and two-way processes to enzymatic hydrolysis using separated hydrolysis and fermentation (SHF) or simultaneous saccharification and fermentation (SSF). The chromatography analysis showed that the hydrogen peroxide hydrolysis is the more effective pretreatment and that SSF has the highest productivity. The ethanol output can minimize the water hyacinth removal cost through some economical and environmental return.